KEPASTIAN HUKUM PEMBERIAN GANTI KERUGIAN MELALUI PUTUSAN PRA PERADILAN : STUDI KASUS PUTUSAN NOMOR 10/PID.PRA/2022/PN.MTR - M. Daffa Wildan Arzaky; Tanudjaja Tanudjaja (Gapenas Publisher, 2023)
The act of law enforcement officers arresting, detaining, prosecuting or being tried against someone without a reason based on the law is an act that is detrimental to human rights. For these actions, the Criminal Procedure Code guarantees legal protection for someone who has experienced acts committed by law enforcement officials without reasons based on the law through a pretrial compensation mechanism. One of the interesting decisions occurred in Decision Number 10/Pid.Pra/2022/Pn.Mtr concerning Pretrial Compensation. The decision granted the plaintiff's demands even though the applicant did not include evidence to corroborate his request to obtain material compensation. The formulation of the problem in this research is what is the ratio decidendi in pre-trial decision NUMBER 10/PID.PRA/2022/PN.MTR regarding compensation? and what are the legal remedies for case NUMBER 10/PID.PRA/2022/PN.MTR. The research method used is normative juridical research with statutory and conceptual approaches. The legal materials used are primary, secondary and tertiary legal materials. The results of the study show that the legal considerations carried out by the judge using the ratio decidendi theory are in accordance with the theory of justice put forward by Aristotle and John Rawls where the judge has rendered a decision in favor of the applicant's request to obtain material losses even though the applicant is unable to show evidence at trial. Then regarding the legal consequences after the pretrial decision, it is known that the government, in this case the ministry of finance, does not yet have a legal basis governing the mechanism for granting compensation in accordance with the mandate of Government Regulation Number 92 of 2015. For this reason, the applicant has the potential to lose his rights again